UJI EFEKTIVITAS EKSTRAK ETANOL DAUN BANDOTAN (Ageratum conyzoides) SEBAGAI ANTIDIARE - Sembiring, Pintata (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
Diarrhea is an abnormal stool that is thinner than usual and occurs more than three times a day. Bandotan leaves have antibacterial properties. This study was an experimental study using 25 rats induced with oleumricin and divided into five groups, the negative control group of 1% CMC- Na, the positive control of Loperamide HCl and the group of bandotan leaf ethanol extract doses of 100 mg/kg, 150 mg/kg and 200 mg/kg. Bandotani leaves (Ageratum conyzoides) as samples were extracted by soaking using 96% ethanol then concentrated by spinning. The results of the phytochemical screening of bandotan leaves obtained flavanoid compounds, saponins, tannins, alkaloids. The results of the anti-diarrhea effect with EEDB doses of 100, 150 and 220 mg/kg showed an anti-diarrhea effect in male rats, the best anti-diarrhea effect was the average EEDB dose of 150 mg/kg. compared doses of 100 and 150 mg/kg. Bandotani leaf extract (Ageratum conyzoides) has antidiarrheal activity induced by oleumricin in male white rats.